Magnetic resonance imaging of human variegated squirrel bornavirus 1 (VSBV-1) encephalitis reveals diagnostic pattern indistinguishable from Borna disease virus 1 (BoDV-1) encephalitis but typical for bornaviruses - Monika Huhndorf; Julia Juhasz; Mike P. Wattjes; Andreas Schilling; Stefan Schob; Ingmar Kaden; Günter Klaß; Dennis Tappe (Emerging Microbes and Infections)
Human bornavirus encephalitis is an emerging disease caused by the variegated squirrel bornavirus 1 (VSBV-1) and the Borna disease virus 1 (BoDV-1). While characteristic brain magnetic resonance imaging (MRI) changes have been described for BoDV-1 encephalitis, only scarce diagnostic data in VSBV-1 encephalitis exist. We systematically analysed brain MRI scans from all known VSBV-1 encephalitis patients. Initial and follow-up scans demonstrated characteristic T2 hyperintense lesions in the limbic system and the basal ganglia, followed by the brainstem. No involvement of the cerebellar cortex was seen. Deep white matter affection occurred in a later stage of the disease. Strict symmetry of pathologic changes was seen in 62%. T2 hyperintense areas were often associated with low T1 signal intensity and with mass effect. Sinusitis in three patients on the first MRI and an early involvement of the limbic system suggest an olfactory route of VSBV-1 entry. The viral spread could occur per continuitatem to adjacent anatomical brain regions or along specific neural tracts to more distant brain regions. The number and extent of lesions did not correlate with the length of patients’ survivals. The overall pattern closely resembles that described for BoDV-1 encephalitis. The exact bornavirus species can thus not be deduced from imaging results alone, and molecular testing and serology should be performed to confirm the causative bornavirus. As VSBV-1 is likely of tropical origin, and MRI investigations are increasingly available globally, imaging techniques might be helpful to facilitate an early presumptive diagnosis of VSBV-1 encephalitis when molecular and/or serological testing is not available.